OC-055 The timed barium esophagram surface areacorrelates with symptom improvement better than column height following treatment in achalasia. (17th June 2017) - Sanagapalli, S; Maynard, J; Plumb, A; Emmanuel, A; Duffy, M; Raeburn, A; Banks, M; Haidry, R; Lovat, L; Sweis, R
Abstract : Introduction: Timed barium esophagram (TBE) is an objective measurement of esophageal emptying in achalasia. Post-therapy reduction of residual barium column height correlates imperfectly with short term symptomatic outcomes. We hypothesise that surface area (SA) of the barium column may be more accurate than height; firstly, by incorporating improvement in esophageal width that often occurs post-therapy, but also by correcting for artificially higher height values due to esophageal contraction occurring. We aimed to compare the correlation of TBE outcome measures of height and SA with symptom improvement post-therapy. Method: Achalasia patients who underwent therapy between 2015–6 and had TBE and Eckardt score (ES) performed at baseline as well as within 6 months post-therapy were included. TBE images were acquired 5 mins following ingestion of 200 mL barium. Barium height was measured between the gastro-esophageal junction and the superior extent of any residual barium column. After manually defining column boundaries, software was used to calculate SA. Adequate symptom relief was defined as ES reduction to ≤3. On TBE, metrics of adequate emptying evaluated were i) post-therapy column height <5 cm, ii)>50% reduction in column height from pre to post-therapy and iii)>50% reduction in column SA from pre to post-therapy. Results: Of 18 patients, 11 had dilatation and 7 POEM. Reductions with therapy of both 5 min barium column height (14.7±8.7 to 7.9±6.0 cm; p=0.01) and SA (52.7±43.5 to 24.5±26.0cm 2 ; p=0.02) were noted. Symptoms also improved; median baseline ES 7 (IQR 5.25–8) improved to 0 (IQR 0–1) post-therapy. However there was poor concordance between post-therapy barium height and symptomatic relief (i.e. post-therapy column >5 cm despite ES ≤3 or vice versa), and the correlation (R) between these two variables was poor. Similar poor concordance was seen when adequate emptying was defined by >50% reduction in column height, but >50% reduction in SA paralleled symptom relief most closely. Conclusion: In TBE performed on achalasia patients post-therapy, reduction in SA of the residual barium column compared with baseline values parallels symptomatic relief more closely than reduction of column height. Disclosure of Interest: None Declared